Topology mining of sensor networks for smart home environments. (19th May 2011) - Wang, Yun; Li, Kai
The capability of a smart digital system heavily depends on the information about its environment. Such information can be acquired by underlying sensor networks. This paper explores the problem of topology mining in sensor networks. We propose a new mechanism, called relative contour, to evaluate topological features of underlying networks, particularly, for boundary recognition and skeleton extraction in an irregular sensor network. We further propose methods to identify boundary and skeleton of the network. The construction of relative contours and follow-up operations are carried out in distributed manner. Simulation results show that our methods perform well with complex topologies.